Influence of Lightning Current Waveshape on the Separation Distance Required between Electrical Equipment and Lightning Protection System - Markowska, R. (Elektronika ir Elektrotechnika, 2013)
The object of this paper is to study the effects of lightning current wave on the flashover distance between LPS and protected equipment on a building roof, calculated based on constant area criterion and including all electromagnetic couplings between building components. The resulting flashover distance has been related to the separation distance estimated according to standard procedures. The analysis indicates that the most severe condition is related to 1/200 us lightning current wave, which leads to the highest value of the flashover distance, much higher than the separation distance required by standards. It was shown also that the flashover distance is linearly dependent on the peak values of lightning current and surge voltage between the protected equipment and LPS. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1485